Three-dimensional characterization of cracks in undisturbed Mile expansive soil using X-ray computed tomography - Sun Danxi; Liu Xian-feng; Yuan Sheng-yang; Pan Gaofeng; Jiang Guanlu; Wang Hailong; Komine Hideo; Olivier Buzzi (Soils and Foundations, 2023)
The distribution of cracks strongly affects the hydro-mechanical behavior and strength of soil. In order to characterize the distribution of cracks in undisturbed expansive soil, X-ray computed tomography (X-ray CT) tests were carried out for one type of undisturbed expansive soil from Mile City, China. Seven undisturbed specimens retrieved from depths between 1 and 4.7 m were used to study the evolution of cracks along the drying path. The characteristics of the cracks were quantitatively studied by 3D parameters extracted from CT images by commercial software. The test results suggested that, with an increase in suction, the total volume of the cracks gradually increased, and one large crack formed due to the merging of sub-cracks before the shrinkage limit. When the suction was larger than the suction corresponding to the shrinkage limit, degradation of the cracks caused by the collapse of the soil structure was observed. Meanwhile, due to the development of sub-cracks, the crack anisotropy caused by the typically oriented primary cracks decreased along the drying path. Finally, a conceptual model of crack development for undisturbed Mile clay was proposed based on the evolution of crack volume, number, shape, and orientation.